Festival of colors - Sehgal, Kabir; Sehgal, Surishtha (Little Simon, 2021)
Spring is here, and it's almost time for Holi, the Indian Festival of Colors. Siblings Mintoo and Chintoo are busy gathering flowers to make into colorful powders to toss during the festival. And when at last the big day comes, they gather with their friends, family, and neighbors for a vibrant celebration of fresh starts, friendship, forgiveness, and, of course, fun!
Keywords: Bilderbuch; Kinderbuch